2009
DOI: 10.1111/j.1743-4580.2008.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Race, and Bridge Building in Economic Justice Coalitions

Abstract: Religious organizations regularly perform key bridge building and political activation tasks in the racialized landscape of living wage organizing in the U.S. As bridge builders, they mediate the varied concerns and cultures of labor, immigrant, and black civil rights organizations through ideology translation, relational repair, and inclusion monitoring. Religious organizations' social location and indigenous leadership development also cultivates levels of political participation among poor people and people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Prodded by insights on intersectionality (see recent reviews and developments by Cho, Crenshaw, & McCall, 2013;Chun, Lipsitz, & Shin, 2013;Verloo, 2013), social movement scholars have increasingly sought to understand how activists negotiate overlapping positional and cultural differences in the social world (e.g., Beamish & Luebbers, 2009;Braunstein, Fulton, & Wood, 2014;Brecher & Costello, 1990;Gamson, 1997;Ghaziani, 2011;Lichterman, 1995Lichterman, , 2005Longard, 2013;Mayer, 2009;Nakano, 2013;Reger, Myers, & Einwohner, 2008;Roth, 2003Roth, , 2008Smith, 2002;Snarr, 2009;Swarts, 2011;Wood, Fulton, & Partridge, 2012;Yukich, 2010). One way that social movement scholars have attempted to address this question is through attention to "bridging work" or "bridge building" in social movements, which is a "form of social movement interaction that focuses explicitly on efforts to overcome and negotiate conflicts that result from different collective identities," usually in a way that takes into account the concerns of all actors involved (Roth, 2003, p. 9; see also Beamish & Luebbers, 2009;Braunstein et al, 2014;Brecher & Costello, 1990;Ghaziani, 2011;Lichterman, 2005;Mayer, 2009;Roth, 2008;Smith, 2002;Snarr, 2009;Wood et al, 2012). Similarly, social movement scholars have begun to shed light on the role of "bridging organizations" in social movements, or organizations that seek "to educate different groups about each other, to reduce fear and hostility based on ignorance by bringing individuals together, and to encourage the valuing of cultural diversity" …”
Section: Previous Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Prodded by insights on intersectionality (see recent reviews and developments by Cho, Crenshaw, & McCall, 2013;Chun, Lipsitz, & Shin, 2013;Verloo, 2013), social movement scholars have increasingly sought to understand how activists negotiate overlapping positional and cultural differences in the social world (e.g., Beamish & Luebbers, 2009;Braunstein, Fulton, & Wood, 2014;Brecher & Costello, 1990;Gamson, 1997;Ghaziani, 2011;Lichterman, 1995Lichterman, , 2005Longard, 2013;Mayer, 2009;Nakano, 2013;Reger, Myers, & Einwohner, 2008;Roth, 2003Roth, , 2008Smith, 2002;Snarr, 2009;Swarts, 2011;Wood, Fulton, & Partridge, 2012;Yukich, 2010). One way that social movement scholars have attempted to address this question is through attention to "bridging work" or "bridge building" in social movements, which is a "form of social movement interaction that focuses explicitly on efforts to overcome and negotiate conflicts that result from different collective identities," usually in a way that takes into account the concerns of all actors involved (Roth, 2003, p. 9; see also Beamish & Luebbers, 2009;Braunstein et al, 2014;Brecher & Costello, 1990;Ghaziani, 2011;Lichterman, 2005;Mayer, 2009;Roth, 2008;Smith, 2002;Snarr, 2009;Wood et al, 2012). Similarly, social movement scholars have begun to shed light on the role of "bridging organizations" in social movements, or organizations that seek "to educate different groups about each other, to reduce fear and hostility based on ignorance by bringing individuals together, and to encourage the valuing of cultural diversity" …”
Section: Previous Literaturementioning
confidence: 99%
“…For instance, in his analysis of church groups that seek to build bridges between racial groups, Lichterman (2005) argues that groups that talk self-critically about their social ties are more likely to "spiral outward" and thus build relationships with individuals outside the group (see also Longard, 2013). Similarly, Snarr's (2009) research on economic justice coalitions highlights the role of bridging organizations in ideology translation, in which activists "help those with different but relatively complementary beliefs understand each other for improved collaboration" (p. 77). Braunstein et al (2014) argue that certain prayer practices are effective in bridging racial and class-based divides among members of faith-based community organizing coalitions because they resonate with individuals across racial and socioeconomic lines (see also Wood et al, 2012).…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…At the meso level, social movements mobilizing at a local level can bring together social groups who were previously divided along lines of age, race, nationality, social class, sex, sexual orientation, gender identity, religion, political identity, and other social differences (see also Gawerc, 2020). Specifically, scholars have shown that the work of social movements at the local level has brought together disparate social groups including working‐class African‐American activists and more privileged white activists (Beamish & Luebbers, 2009; Snarr, 2009); U.S. citizens and undocumented immigrants (Enriquez, 2014; Yukich, Fulton, & Wood, 2019); straight people and LGBTQ (lesbian, gay, bisexual, transgender, and queer) people (Coley, 2014, 2020; Ghaziani, 2011); and Christians, Jews, Muslims, and other people of faith (Braunstein, Fulton, & Wood, 2014).…”
Section: Prosocial Outcomes Of Social Movementsmentioning
confidence: 99%
“…Most of the time, scholars have considered bridge building to be an unintended or secondary outcome of social movement activism. Specifically, in their efforts to mobilize diverse social groups to achieve other desired goals, movement leaders may find they must build bridges between mobilized groups who are wary of each other (see, for example, Beamish & Luebbers, 2009; Braunstein et al, 2014; Enriquez, 2014; Snarr, 2009; Yukich et al, 2019). Nevertheless, bridge building can also be conceptualized as a primary, intended goal of social movement activism.…”
Section: Prosocial Outcomes Of Social Movementsmentioning
confidence: 99%